Artes indígenas na escola não indígena: conversas com docentes de artes visuais da prefeitura do Recife - Costa, Flávia Roberta Alves (2023)
The present investigation was developed in the line of research Visual Arts and its educational, cultural and creative processes, in the Associated Graduate Program in Visual Arts UFPE/UFPB – Master in Visual Arts. It aimed to understand how indigenous themes are approached in the field of Visual Arts in the final years of Elementary School of Full-time Municipal Schools of the Recife City Hall. The theoretical framework addresses decolonial thinking (CANDAU, 2008, 2010, 2020; QUIJANO, 1992, 2005, 2007; WALSH, 2005, 2009, 2018), art teaching (BARBOSA, 1998, 2008, 2009, 2010, 2011; RICHTER, 2003; MOURA, 2018) and contemporary indigenous art (ESBELL, 2021; JESUS, 2019, 2020, 2021), in addition to the references of studies found in the state of knowledge surveyed on the subject. The research takes a decolonial approach, as it is an investigation that seeks to overcome hegemonic epistemological standards and that discusses how the artistic productions of the native peoples of Brazil are seen and understood in these schools, proposing this thinking with the teachers based on conversation as a research methodology (FERRAÇO and ALVES, 2018; RIBEIRO, SOUZA and SAMPAIO, 2018). We used Content Analysis (BARDIN, 2011) to understand the guidelines on indigenous themes contained in the Teaching Policy of the Municipal Network of Recife and to study the conversations with teachers under the theoretical bias of decolonial thinking. The analysis carried out allowed us to understand that even though the inclusion of indigenous themes in the normative documents is perceived, the continuity of training and actions directed to this study was not observed in the researched network. In addition to this gap, the precariousness and restriction of Visual Arts teaching materials related to indigenous themes at the national and local levels. Even with these limitations, we perceive the efforts of teachers to bring their research and individual experiences to the classroom. We agree that it is necessary to denaturalize the coloniality processes that are introjected not only in the curricula and teaching materials of arts, but mainly in our individual and collective imaginary and in the knowledge that we privilege with and from subaltern subjects, in a procedural and permanent path.